Features that Guarantee High-Quality Authorship for Social E-Commerce - Anwar Basalamah; Edvi Gracia Ardani; Widya Novitasari (Universitas Pendidikan Ganesha, 2024)
Demand for flower arrangements from various market segments in Indonesia is growing along with increasing consumer interest in using social media-based online sales platforms. Creative money bouquet product ideas are one of the newest trends in the flower arrangement business. The risk of lower product quality often arises after the delivery process, where the product received does not match the image published on the platform. Customer dissatisfaction often occurs in similar transactions due to the role of product packaging in increasing the quality of the money bouquet product. The aim of this research is to find out how appropriate product packaging can increase the selling power of a product on the market. This research uses a qualitative with a narrative approach as the research methodology. The sampling method used in this research was purposive sampling. The research object is @Moneyrist.id and The subjects in this research are IE-social customers.commerce. Observation and unstructured interviews were used to collect data, with the findings showing that product packaging is designed according to customer needs and must consider safety factors. This is a guarantee that the product will reach the customer's hands in good condition. The implications of this research focus on increasing customer trust through features that ensure the quality of money arrangements on social e-commerce platforms, with a case study on Moneyrist.id.